Subjective Well-Being From a Just-World Perspective: A Multi-Dimensional Approach in a Student Sample - Nartova-Bochaver, Sofya; Donat, Matthias; Rüprich, Claudia (Frontiers in Psychology, 2019)
In a cross-sectional study with N = 627 individuals (Mage = 22.8, SDage = 7.3, 147 males, 480 females, 106 non-religious, 456 religious), we investigated personal belief in a just world as a resource for undergraduates’ subjective well-being and expected a positive relation between both constructs due to recent studies. We not only aimed at replicating but also extending recent findings by investigating a Russian sample, measuring different dimensions of well-being, and considering self-esteem and resilience as potential mediators in the relation of belief in a just world and well-being. We also controlled for confounding effects of age, gender, religiosity, and general belief in a just world. The findings show that personal belief in a just world related to all investigated indicators of well-being (depressive symptoms, positive and negative affect, and mental well-being). Self-esteem mediated all relations between personal belief in a just world and indicators of subjective well-being whereas resilience mediated relations of personal belief in a just world to positive affect and mental well-being. The pattern of results persisted when we controlled for age, gender, religiosity, and general belief in a just world. Our results confirm that the personal belief in a just world functions as a psychological resource in undergraduate students.